QUYI AMUDARYO DAVLAT BIOSFERA REZERVATI HUDUDIDA TARQALGAN DARYO CHIGIRTCHISI EKOLOGIYASI - Bekniyazova D.B, Bekniyazova D.B; Turdibaev Q.P., Turdibaev Q.P.; Ametova N.I., Ametova N.I.; Arzıbaev D.F., Arzıbaev D.F.; Matekova G.A, Matekova G.A (Actual problems and prospects of the study of the fauna, 2024)
The scientific work presents materials on the ecology of the common tern (Sterna hirundo), common in the territory of the Lower Amu Darya State Biosphere Reserve. The authors studied the distribution of the species, migration periods, nesting, egg-laying and nutrition.